Geometry in Ethnomathematics Research Publication: Bibliometric Analysis - Supriyadi, Edi; Turmudi; Jarnawi Afgani Dahlan; Dadang Juandi (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
This study examines the implementation of ethnomathematics in geometry, in addition to the challenges and benefits of this approach. This study also emphasizes the dearth of bibliometric studies in this area and provides a Scopus-based bibliometric analysis of research on geometry in ethnomathematics. This study examines the evolution of research publications, the most cited articles, the most prolific writers, and current trends in research. This paper uses bibliometric analysis using Rstudio Biblioshiny as its methodology. The study discovered that studying geometry from an ethnomathematics perspective provides benefits such as enhancing learning interaction activities and conceptual comprehension. However, the lack of understanding about the ethnomathematics approach and how to incorporate it into teaching geometry, the teacher's lack of knowledge about geometry content knowledge, and the teacher's aversion to change are impediments to the use of this technique. Researchers that desire to discover research gaps for future studies are anticipated to find this study's findings valuable.